Impacts of trade liberalization on poverty and inequality in Argentina - Cicowiez, Martín; Díaz-Bonilla, Carolina; Díaz-Bonilla, Eugenio (World Bank, 2009)
Using the most recent estimates of agricultural price distortions, this chapter studies the economic, poverty, and income inequality impacts of both global and domestic trade reform in Argentina, with a special focus on export taxes. Argentina offers an interesting case study as the only large agricultural exporter that has, at many points in its history, applied export taxes to several of its agricultural products. The chapter combines results from a global economy-wide model (World Bank’s Linkage model), a national CGE model, and microsimulations. The results suggest that liberalization of world trade (including subsidies and import taxes, but not export taxes), both for agricultural and nonagricultural goods, reduces poverty and inequality in Argentina. However, if only agricultural goods are included, indicators for poverty and inequality do not improve and even deteriorate somewhat. This is particularly the case if export taxes are eliminated. The chapter discusses the possible reasons for those results, offers some caveats, and suggests some lines for further research.